Small Business Owners` Perception City Councils` Role in Small Businesses Creation in Their Municipalities. Case of Kumba City Council (International Journal of Scientific Research and Management (IJSRM), 2023)
The study seeks to evaluate the perception of the role of City Councils in the creation of small businesses. Using a descriptive research design, 150 questionnaires were administered to these owners by convenience. Data was analysed using descriptive statistics through the Statistical Package for Social Sciences (SPSS 2022 version). Results reveal that the majority of small business owners (51.3%) believe that the City Council does nothing to encourage the creation of small businesses. It was recommended that the City Council should act more as a facilitator for small businesses and encourage their creation and even their sustainability. This is because more businesses mean more revenues, and improved living standards both for the business owners and the City Council and its workers.